A Hardware Testbed of Grid-Connected Wind-Solar Power System - Soetedjo, Aryuanto; Lomi, Abraham; Puspita, Bayu Jaya (International Journal of Smart Grid and Sustainable Energy Technologies, 2017)
This paper presents the development of hardware testbed for implementing grid connected wind-solar power system. A solar simulator using halogen lamp is employed to simulate the sun irradiation. The wind power simulator is developed by coupling the DC motor and the DC generator. A grid tie inverter is employed to connect the power from the solar and wind power system with the grid system. The experimental results show that the developed testbed could be used for testing the hybrid power system in the real hardware.